2018
DOI: 10.1016/j.ijcard.2018.03.082
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a fixed dose combination (polypill) in secondary prevention of cardiovascular diseases in India: Within-trial cost-effectiveness analysis of the UMPIRE trial

Abstract: The polypill strategy was cost-saving compared to usual care among patients with or at high risk of CVD in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 48 publications
2
27
0
1
Order By: Relevance
“…In a recent analysis comparing the implementation of a cardiovascular polypill (aspirin, statin and angiotensin-converting enzyme (ACE)-inhibitor) compared with multiple monotherapy in adults with a history of myocardial infarction in the UK, the FDC-based therapy proved to be cost-effective: the only improvement in adherence (estimated to be about 20%) was estimated to prevent 15% of fatal and non-fatal cardiovascular events (47 out of 323/1000 patients). 11 Cost-effectiveness of FDC has been demonstrated even in low–middle income countries such as India: interestingly, it appears to be greater in patients with diabetes, 12 further reinforcing the clinical relevance of the present analysis.…”
supporting
confidence: 70%
See 3 more Smart Citations
“…In a recent analysis comparing the implementation of a cardiovascular polypill (aspirin, statin and angiotensin-converting enzyme (ACE)-inhibitor) compared with multiple monotherapy in adults with a history of myocardial infarction in the UK, the FDC-based therapy proved to be cost-effective: the only improvement in adherence (estimated to be about 20%) was estimated to prevent 15% of fatal and non-fatal cardiovascular events (47 out of 323/1000 patients). 11 Cost-effectiveness of FDC has been demonstrated even in low–middle income countries such as India: interestingly, it appears to be greater in patients with diabetes, 12 further reinforcing the clinical relevance of the present analysis.…”
supporting
confidence: 70%
“…11 Cost-effectiveness of FDC has been demonstrated even in low-middle income countries such as India: interestingly, it appears to be greater in patients with diabetes, 12 further reinforcing the clinical relevance of the present analysis.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…12 It is also cost-saving when compared to usual care. 13 Different formulations of polypill were used in several studies worldwide. [14][15][16][17][18][19][20][21] The results of a pilot study from Iran suggested that a polypill consisted of aspirin 81 mg, enalapril 2.5 mg, atorvastatin 20 mg and hydrochlorothiazide 12.5 mg was well tolerated and participants' compliance to the polypill was satisfactory, with modest reductions in blood pressure and lipid levels.…”
Section: Introductionmentioning
confidence: 99%